2014
DOI: 10.1371/journal.pbio.1001959
|View full text |Cite
|
Sign up to set email alerts
|

Differentially Timed Extracellular Signals Synchronize Pacemaker Neuron Clocks

Abstract: Circadian pacemaker neurons in Drosophila are regulated by two synchronizing signals that are released at opposite times of day, generating a rhythm in intracellular cyclic AMP.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
51
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 48 publications
(55 citation statements)
references
References 67 publications
4
51
0
Order By: Relevance
“…Inputs from other clock neurons help synchronize individual s-LNv molecular clocks and regulate their neuronal activity (Collins et al, 2012; Collins et al, 2014). Since EM studies of s-LNv axonal projections had revealed they have input synapses (Yasuyama and Meinertzhagen, 2010), we tested if s-LNv plasticity is also associated with altered accumulation of post-synaptic components.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Inputs from other clock neurons help synchronize individual s-LNv molecular clocks and regulate their neuronal activity (Collins et al, 2012; Collins et al, 2014). Since EM studies of s-LNv axonal projections had revealed they have input synapses (Yasuyama and Meinertzhagen, 2010), we tested if s-LNv plasticity is also associated with altered accumulation of post-synaptic components.…”
Section: Resultsmentioning
confidence: 99%
“…Immunocytochemistry was carried out as in (Collins et al, 2012; Collins et al, 2014). Antibodies are described in the supplementary information.…”
Section: Methodsmentioning
confidence: 99%
“…Our work builds on a broad consensus that Drosophila PDF signaling proceeds early in the photophase (Park et al , 2000; Cusumano et al , 2009; Zhang et al , 2009; Im et al , 2011; Collins et al, 2014; Choi et al , 2014). The specific thought is that ligand availability (via PDF release) is greatest in the morning.…”
Section: Discussionmentioning
confidence: 99%
“…The neurons interact extensively via conventional neurotransmission and via neuropeptidergic signals to organize temporal information across the network and to mediate entrainment to environmental signals (Collins et al , 2014; Chung et al , 2009; Guo et al , 2014, Hermann-Luibl et al , 2014; Kunst et al , 2014; Parisky et al , 2008; Renn et al , 1999; Shafer et al, 2008). …”
Section: Introductionmentioning
confidence: 99%
“…Notably, in DD, the s-LNvs operate at the pinnacle of a hierarchy as they enforce a majority of other oscillators to realign their clock program in accordance with the sLNv pace (Stoleru et al 2005). In contrast, messages from the non-PDF clocks have considerably subdued influence on the running of the master pacemaker in DD (Stoleru et al 2005;Picot et al 2007;Collins et al 2014). Recently, however, the existence of a centralized monopolar circuit organization in DD has been seriously challenged.…”
Section: Layout Of the Network In Constant Conditionsmentioning
confidence: 99%